Treatment of recurrent aphthous stomatitis major with metronidazole and ciprofloxacin - M. Jusri; Nurdiana Nurdiana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Recurrent aphthous stomatitis (RAS) are painful oral ulcerations that recur from days to months or even years. It represents the most common lesion of the oral mucosa with prevalence ranging from 15% to 30%. Although the clinical characteristics of RAS are well defined, the precise etiopathogenesis of RAS remains unclear. Since the etiology of RAS remains unknown, there is no definitive treatment. RAS responds quite well to the use of topical or systemic antiinflammatory drugs, particularly corticosteroids. Purpose: The objective of this paper is to discuss the treatment of RAS with secondary infection. Case: This paper reported a case of 22-year-old man with multiple oral ulcers that did not heal for 7 months. Case Management: These ulcers were diagnosed as RAS major with secondary infection that caused by normal oral flora (aerobic and anaerobic bacteria) and treated with metronidazole (topical and oral) and ciprofloxacin (oral). These lesions healed in 3 weeks with scars. Conclusion: Large ulcer without signs of malignancy that contaminated with normal oral flora will delayed in healing, but with rational treatment RAS mayor with secondary infection has good prognosis.